Spatial Autocorrelation on Public Facility Availability Index with Neighborhoods Weight Difference - Khursatul Munibah; Widiatmaka Widiatmaka; Hermanu Widjaja (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. The level of regional development is marked by high availability of public facilities, such as education, health, economic, social facilities and their accessibility. A higher of index of public facility availability means a region can support human activities well, including the economic sector. Spatial patterns of public facility availability in Cianjur Regency were analized by global and local spatial autocorrelation based on the Moran's index and the local indicator spatial association (LISA) index, respectively. A spatial weighted matrix (wij) for Moran'I and LISA calculated based on nearest neighbor, neighbor boundary length and neighbor distance. The result showed that differences in the spatial weighted matrix of Moran's index does not affect the spatial pattern but they do affect the Moran's I values for nearest neighbor, neighbor boundary length and neighbor distance, at 0.30; 0.22 and 0.33, respectively. Differences in the spatial weighted matrix of LISA index showed that 97% of districts have the same scatter plot and only 3% of districts have different scatter plot. The spatial pattern type of public facility evailability in Cianjur Regency is cluster where the nothern Cianjur cluster is in HH category and the central-southern Cianjur cluster is in the LL category.Keywords. LISA index, Moran's index, spatial pattern, spatial weighted matrix.Abstrak. Tingkat perkembangan wilayah ditandai dengan ketersediaan fasilitas umum yang tinggi seperti fasilitas pendidikan, kesehatan, ekonomi sosial dan aksessibilitas. Indeks ketersediaan fasilitas umum yang tinggi dapat mendorong aktivitas manusia yang baik, termasuk dalam sektor ekonomi. Pola spasial dari indeks ketersediaan fasilitas umum di Kabupaten Cianjur dianalisis dengan global dan local spasisl autokorelasi yang dihitung masing-masing berdasarkan pada Indeks Moran dan indeks LISA (local indicator spatial association). Bobot spasial yang digunakan dalam perhitungan global dan lokal spasial autokorelasi adalah nearest neighbor, neighbor boundary length and neighbor distance. Hasil menunjukkan bahwa perbedaan bobot spatial pada global spatial autocorrelation tidak memberikan pengaruh terhadap pola spasial tetapi berpengaruh pada nilai Moran Index yaitu 0.30; 0.22 and 0.33 masing-masing untuk nearest neighbor, neighbor boundary length dan neighbor distance. Perbedaan bobot spasial di local autokorelasi menunjukkan bahwa 97% kecamatan di Kabupaten Cianjur memiliki scatter plot yang sama dan hanya 3% kecamatan memiliki scatter plot yang berbeda. Pola spasial ketersediaan fasilitas umum di Kabupaten Cianjur adalah kluster dimana kluster Cianjur Utara dengan kategori HH dan kluster Cianjur Tengah-Selatan dengan kategori LL. Kata kunci. Indeks LISA, indeks Moran, pola spasial, bobot spasial